Predicting climate change impacts on distribution and conservation of critically endangered Picea neoveitchii using MaxEnt - Xue, Ninghan; Li, Kaiyuan; Chen, Kexin; Li, Panpan; Ji, Xinmiao; Ma, Zhilin; Ji, Wenli (Frontiers in Forests and Global Change, 2024)
Picea neoveitchii Mast., an endemic and rare species in China, classified as Critically Endangered (CR) in the IUCN Red List of Threatened Species, possesses significant research value due to its unique biological characteristics that contribute to plant taxonomy and the conservation of the genus Picea. Despite its excellent timber quality and high ornamental value, it has not been widely used and well protected. This study employed the MaxEnt modeling approach, incorporating field survey data on species distribution and species distribution data collected online, along with climatic and environmental data sourced from IPCC reports and climate databases. It assessed the current and future distribution ranges, influential variables, and conservation status of P. neoveitchii. The results indicate that Minimum Temperature of the Coldest Month, Annual Precipitation, Temperature Seasonality, and Altitude are the key factors influencing the distribution of P. neoveitchii. Across all future climate scenarios, the suitable habitat for P. neoveitchii consistently exhibits a trend of shifting northwestwards. Under SSP2-4.5, SSP5-5.8 scenario, the suitable area decreases in all periods. Under SSP1-2.6 scenario, the suitable area decreases, except the period from 2080 to 2,100, which sightly increases. Notably, the proportion of habitat within natural reserves increased. To conserve P. neoveitchii, it is necessary to adopt in-situ and ex-situ conservation measures, conserve germplasm resources through seed banking and tissue culture, and implement strict enclosure policies to minimize human disturbance and promote natural regeneration. These findings highlight the need for targeted conservation measures to address the ongoing threat to this species.